THE INFLUENCE OF HUMAN RESOURCE COMPETENCIES AND ACCOUNTING SYSTEMS ON REPORT QUALITY FINANCE WITH INTERNAL CONTROL AS A MODERATING VARIABLE - Januarty, Harumi; Ratnawati, Ratnawati; Rokhman, M Taufiq Noor; Ningsih, Ayu Agus Tya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The purpose of this study is to determine the direct influence of human resources (HR) and accounting systems on the quality of financial reports. The influence of human resources and accounting systems with the role of internal control as a moderating variable in the Malang Regency Government environment. This study uses a quantitative approach by distributing questionnaires to 90 respondents from 25 Regional Apparatus Organizations (OPD), two sections, two agencies, and one inspectorate directly related to the preparation of financial reports. The analysis techniques used include multiple linear regression and moderated regression analysis (MRA). The results of the study indicate that HR competency does not significantly influence the quality of financial reports. The accounting system influences the quality of financial reports. In addition, internal control does not significantly moderate the influence of human resource competency on the accounting system. Finally, internal control moderates the influence of the accounting system on the accounting system.